Konsep Umum tentang Kepemimpinan - Lestari, Fajar Puji (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2022)
Since ancient times, humans who live in groups must have known the term leadership or other designations that mean the same. Leadership is absolutely necessary when there is a cooperative interaction between two or more people in achieving goals. Leadership is concerned with someone influencing the behavior of others for a purpose. More broadly, leadership is the process of the leader creating a vision, influencing the attitudes, behavior, opinions, values, norms, and so on of its members to realize the vision. Leadership touches various aspects of human life such as how to work, neighbors, society, and even a state. Leadership, management, and administration are interconnected efforts and have a very close relationship. Leadership is the essence of management, and management is the essence of administration.